2009
DOI: 10.1063/1.3276280
|View full text |Cite
|
Sign up to set email alerts
|

Quantum transport in alkane molecular wires: Effects of binding modes and anchoring groups

Abstract: Effects of binding modes and anchoring groups on nonequilibrium electronic transport properties of alkane molecular wires are investigated from atomic first-principles based on density functional theory and nonequilibrium Green's function formalism. Four typical binding modes, top, bridge, hcp-hollow, and fcc-hollow, are considered at one of the two contacts. For wires with three different anchoring groups, dithiol, diamine, or dicarboxylic acid, the low bias conductances resulting from the four binding modes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 55 publications
4
17
0
Order By: Relevance
“…Our DFT results are in reasonable agreement with previous DFT studies showing decay factors in the range 0.83–1.01 and conductance resistances in the range (0.09–0.28) G 0 [810]. While the β values obtained with GW are rather close to the DFT calculated ones, the contact conductance is reduced by a factor of 3–5, depending on the coverage.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our DFT results are in reasonable agreement with previous DFT studies showing decay factors in the range 0.83–1.01 and conductance resistances in the range (0.09–0.28) G 0 [810]. While the β values obtained with GW are rather close to the DFT calculated ones, the contact conductance is reduced by a factor of 3–5, depending on the coverage.…”
Section: Resultssupporting
confidence: 91%
“…Although previous studies based on DFT yielded β values within the experimental range, the contact conductance, G c , is typically overestimated by around an order of magnitude [310]. A study based on the many-body configuration interaction method has shown similar β values, but slightly reduced G c values, as compared to DFT [52].…”
Section: Introductionmentioning
confidence: 99%
“…Such a device is becoming even more interesting because different laboratories reported transport data that were quantitatively consistent with each other [19][20][21]. In addition, theoretical researchers also do their utmost to explore the effects of length, end groups, bonding sites, and interface states on the transport properties of alkane molecular junction [22][23][24]. The same conclusion was obtained from the above experimental and theoretical works: the resistance of alkane molecule is enormous.…”
Section: Introductionsupporting
confidence: 69%
“… 16 18 Thus, alternative anchoring groups have been studied extensively both theoretically and experimentally. These include, for example, pyridines 10 , 19 21 , isocyanides (−NC), 7 , 22 , 23 cyanides (−CN), 5 , 10 , 22 the above-mentioned selenolates (−Se), 24 , 25 amines (−NH 2 ), 10 , 26 28 carboxyl-acids (−COOH), 26 , 29 and fullerenes (C 60 ). 30 32 These investigations showed that, depending on their donor and acceptor character, anchoring groups can have a profound impact on the level alignment, 9 i.e., the relative energetic position of the HOMO (highest occupied molecular orbital) and the LUMO (lowest unoccupied molecular orbital) with respect to the metal Fermi level.…”
Section: Introductionmentioning
confidence: 99%